2000
DOI: 10.1002/1096-8644(200012)113:4<473::aid-ajpa3>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Fourier analysis of acetabular shape in Native American Arikara populations before and after acquisition of horses

Abstract: The goal of this study was to identify changes in acetabular morphology associated with the use of horses by Native Americans. Previous studies reported "elongate" acetabula in horseback-riding members of the Omaha and Ponca populations. Such a difference in acetabular shape is a potentially useful osteological marker of habitual horseback riding. This report compares acetabula of adult males from two Native American Arikara populations known to have differed substantially in their use of horses. Population sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 8 publications
0
15
0
3
Order By: Relevance
“…While Arikara males hunted throughout the period examined, they probably became more reliant on horses as a means of terrestrial mobility after A.D. 1740 [13,45], which should result in a greater femoral midshaft circularity or even a ML expansion through time [55,75]. However, no significant changes in femur midshaft shape (I ap /I ml ) were observed through time in the Arikara.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Arikara males hunted throughout the period examined, they probably became more reliant on horses as a means of terrestrial mobility after A.D. 1740 [13,45], which should result in a greater femoral midshaft circularity or even a ML expansion through time [55,75]. However, no significant changes in femur midshaft shape (I ap /I ml ) were observed through time in the Arikara.…”
Section: Discussionmentioning
confidence: 99%
“…If anything, the importance of hunting may have declined through time because the Arikara became more dependent on trade with nomadic tribes for meat and hides [49]. The main differences in male activities are probably associated with the introduction of horses and rifles and increased warfare after A.D. 1740 [13,19,45]. The horse most likely increased the hunting efficiency of males, and as warfare increased during the DC, males focused more of their energy on combat related activities.…”
Section: Arikaramentioning
confidence: 99%
“…Despite this prediction, however, only a limited number of studies have analysed the morphological characteristics of the primate acetabulum from an anthropological perspective (Schultz, 1969;MacLatchy and Bossert, 1996;Canillas et al, 2011;Hogervorst et al, 2011;Bonneau, 2013;Hammond et al, 2013a). Although some anthropology-focused authors have analysed and contributed to the research on the morphology and variability of the human acetabulum (Havelock, 1893;Erickson et al, 2000;Rissech et al, 2001;Mafart, 2005;Bonneau et al, 2012), most of the information available has been obtained from studies conducted for medical purposes (Bullough et al, 1973;Müller-Gerbl et al, 1993;Feugier et al, 1997;Witte et al, 1997;Thompson et al, 2000;Gupta et al, 2001;Varodompun et al, 2002;Lavy et al, 2003;Leunig et al, 2003;Zilber et al, 2004;Govsa et al, 2005;Sampson, 2005;Tallroth and Lepist€ o, 2006;Ganz et al, 2008;Vandenbussche et al, 2008;K€ ohnlein et al, 2009;Krebs et al, 2009;Pollard et al, 2010;Nakahara et al, 2011;Zeng et al, 2012). Other studies have examined load transfer across the hip bone and the hip joint (Eckstein et al, 1994;Dalstra and Huiskes, 1995;Lazennec et al, 1997;Witte et al, 1997) and the thickness and stress of the cartilage in humans (Kur...…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, age does not seem to be a bias factor for the changes of the acetabular shape as it is not related to degenerative processes (Baillif‐Ducros et al, ). Erickson et al () found no significant correlation between the estimated age at death and the coefficients used in a Fourier analysis of the acetabular shape.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of the acetabular shape relied on direct measurements of the vertical and horizontal diameters of the acetabulum and the calculation of an index, following the approach taken by Baillif‐Ducros et al () and Sarry et al () that we also previously experimented (Berthon et al, ). Although the Fourier analysis used by Erickson et al () seems particularly relevant to capture the changes of the shape of the entire acetabular rim, several portions of the acetabular rim are frequently not preserved in ancient materials. Second, the vertical and horizontal diameters allow assessing the anterior‐superior rim expansion previously described (Baillif‐Ducros et al, ; Erickson et al, ).…”
Section: Methodsmentioning
confidence: 99%